The eastern provinces of the Dominion of Canada with Newfoundland [and] Mexico, Central America and West Indies. - Ivison, Blakeman, Taylor & Co. (Ivison, Blakeman, Taylor & Co., 1875)
Maps show late nineteenth century geography and settlements in the eastern provinces of Canada, Newfoundland, Mexico, Central America, and the West Indies. Relief shown by hachures. No scale indicated.